Laser polymer welding process: Fundamentals and advancements. (2022) - Anwer, Ghulam; Acherjee, Bappa
Abstract: Laser polymer welding provides a feasible alternative where traditional polymer joining processes have reached their limits. The flexibility of this process is unparalleled, and the weld quality is superior to that of most traditional polymer joining processes. A variety of laser irradiation techniques are devised and effectively utilized in laser welding of polymers. The polymer compositions, as well as optical and thermal characteristics, are significant factors influencing the laser polymer welding process. For a wide variety of polymers, laser polymer welding produces weld strength equivalent to the strength of the substrate material. Lasers are utilized for more than only polymer welding; they are also used to weld hybrid structures consisting of polymer-metal, polymer-ceramics, polymer-glass, polymer-wood composites, etc. This paper presents an overview of the process fundamentals and advancements in laser polymer welding process.